Tinjauan Literatur: Dampak Transformasi Digital terhadap Pengambilan Keputusan di Lembaga Pemerintahan - Ma'sum, Aziz; Purwanto, Heri; Nugraha, Rikky Wisnu (Jurnal Algoritma, 2025)
The development of information and communication technology (ICT) has fundamentally changed the way government agencies provide services and make decisions. Digital transformation has now become a strategic necessity for realizing efficient, transparent, and adaptive governance in line with the changing times. This study aims to analyze the impact of digital transformation on decision-making in government institutions through a literature study approach. The method used is a Systematic Literature Review (SLR) by examining 10 relevant national scientific articles published in the period 2020–2025. The analysis was conducted qualitatively using content analysis techniques to identify the main themes, benefits, and challenges of digitization on the public decision-making process. The results show that digital transformation improves bureaucratic efficiency, strengthens transparency, and expands public participation in policy formulation. The use of technologies such as e-Government, artificial intelligence (AI), and big data analytics enables faster, more accurate, and evidence-based decision-making. However, its success is highly dependent on the readiness of human resources, digital infrastructure, and data security. In conclusion, digital transformation is not merely a technological innovation, but also a key driver towards a smart, transparent, and data-driven government system.